2013
DOI: 10.1074/jbc.m112.437780
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Acts as a Partial Inverse Agonist to Metabotropic Glutamate Receptor with a Single Amino Acid Mutation in the Transmembrane Domain

Abstract: Background: Conformational change of transmembrane domain of mGluR upon glutamate binding is unknown. Results: Moderate steric hindrance between helices VI and VII of mGluR caused constitutive activation and severe steric hindrance caused deactivation. Conclusion: Proper outward movement of helix VI is a critical determinant of activation of mGluR like rhodopsin. Significance: Underlying activation mechanism is common across families of GPCRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…We next measured the G protein activation ability of the visual pigments by a [ 35 S]GTPγS binding assay in complete darkness (under infrared light). The [ 35 S]GTPγS binding assay is a commonly used technique to evaluate the G protein activation rate of G protein-coupled receptors by measuring the GDP-GTPγS exchange rate of G proteins in vitro 11 (See Methods). The concentrations of visual pigments in the aliquots were compared by Western blotting analysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We next measured the G protein activation ability of the visual pigments by a [ 35 S]GTPγS binding assay in complete darkness (under infrared light). The [ 35 S]GTPγS binding assay is a commonly used technique to evaluate the G protein activation rate of G protein-coupled receptors by measuring the GDP-GTPγS exchange rate of G proteins in vitro 11 (See Methods). The concentrations of visual pigments in the aliquots were compared by Western blotting analysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This studies claimed that overexpression of the GRM8 gene might be used as indicator in schizophrenia pathogenesis . [24][25] Another down-regulated gene in active group was HTR2A that was shown to express serotonin receptor with various important roles. If there were abnormalities in the HTR2A, some pathogenesis could take place for instance obsessive-compulsive disorder, susceptibility to schizophrenia and major depressive disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Heterologous expression of mGluR3 in HEK293 cells for in vitro biochemical assay was performed according to previously reported methods (20). The plasmid DNA (10 μ g/100-mm dish) of mGluR3 or pCAG vector (mock) was transfected into HEK293 cells growing to ~40% confluency in DMEM/F12 supplemented with 10% FBS by the calcium-phosphate method.…”
Section: Heterologous Expression and Membrane Preparation For In Vitrmentioning
confidence: 99%
“…The ECDs function as an obligatory dimer, where dimeric reorientation occurs upon ligand binding (14,15). The conformational change in ECDs promotes the dimeric rearrangement of TMDs (16)(17)(18), activating a protomer of the TMD dimer (19,20). Single-molecule tracking (SMT) analysis demonstrated that the average diffusion coefficient (D Av ) of mGluR3 quantitatively reflects receptor activity.…”
Section: Introductionmentioning
confidence: 99%